Análisis deontológico en la práctica profesional de los comunicadores sociales que difunden contenidos informativos en el Canal 6 de la ciudad de Babahoyo, año 2020 - Onofre Pisco, Jessica Cristina (2020)
This case study specifies the arguments that must be incorporated into a code of ethics for the exercise of the profession of social communicator on channel 6 of television in the city of Babahoyo and whose contents are part of a productive debate in university classrooms of the Career of Social Communication of the Technical University of Babahoyo; as one of the best Alma Mater in Ecuador. The quality of social communication concerns the communicators themselves, but also the media and the citizens who receive the information. The inquiry is structured in this case study: where the social communicator is analyzed deontological, as an element of self-regulation of the content of the information that is discharged on channel 6 of television in the city of Babahoyo. We have the definition of the problem, the justification, the objectives, actors and population segment, the theoretical support and the foundations of the Code of Ethics for TV social communicators; methodological strategies, type, design of the research; applied techniques, results obtained and the respective recommendation that is oriented to the application of ethical principles aimed at renewing the professional practice of the social communicator in the television newscasts of channel 6 in primetime of the city of Babahoyo in the year 2020.